Explanatory videos in the context of learning processes: An interdisciplinary interpretative interaction analysis of production and reflection processes - Taha Ertuğrul Kuzu; Christian Ratzke (Journal of Pedagogical Research, 2024)
The article focuses the use and reflection of explanatory videos in pedagogical contexts from an interdis-ciplinary perspective and with regard to teacher reflection and production processes in a joint primary school pedagogical study (with a focus on mathematical learning processes) and Catholic religion educa-tion study (with a focus on secondary school teacher education). With an explorative research question and an interpretative qualitative research design, teachers' reflections of explanatory videos produced by learners as well as teachers are analyzed abductively to gain in-depth insights into potentials and obstacles of the usage of explanatory videos in the context of learning processes. In the primary school pedagogical study, students produce multilingual explanatory videos (n = 18) of the 'Auxiliary task', a mental calculation strategy, which the multilingual teachers reflect (n = 6), and in the Catholic religion education study, teachers produce explanatory videos for making 'encountering' processes possible (n = 17) and both studies are linked with a joint research question. The main insights into potentials and obstacles are that explanatory videos can be used didactically for a) identifying student's subject-and-language-related needs, b) 'decelerated' valuation processes and c) iterative revisions of non-viable video productions as well as biases and beliefs of teachers.